Penerapan Sistem Informasi Manajemen Rumah Sakit di RSUD Dr. Sam Ratulangi Tondano - Tangel, Pricillia T.; Manampiring, Aaltje E.; Kapantow, Nova H. (e-CliniC, 2024)
Abstract: Hospital management information system (HMIS) is an integrated information system prepared to handle the entire process of hospital management and services. This study aimed to analyze the implementation of hospital management information systems at RSUD Dr. Sam Ratulangi Tondano. This was a qualitative case study with in-depth interviews and observation methods. Samples were four informants. Data analysis is a content analysis through the data reduction stage, data presentation in a matrix, and the validity of the research results using source and method triangulation to draw conclusions. The results showed that based on infrastructure indicators, there was a lack of available computers in each section, the internet network quality was inadequate, due to a lack of budget allocation for HMIS. Based on human resource indicators, there was a lack of qualified and competent IT personnel as well as indiscipline on duty, absence of a strict reward and punishment system, that actually disrupted the flow of services in the hospital.  Based on indicators of the operational procedure system, it is in accordance with the existing standards of the hospital to carry out the duties and functions according to their respective duties. In conclusion, the application of HMIS at RSUD Dr. Sam Ratulangi Tondano related to the quality of infrastructure and human resource indicators is still lacking, on the other hand the standard operating procedure indicators are good which are regulated directly by the hospital leadership. Keywords: hospital management information system; infrastructure; human resources; standard operating procedures    Abstrak: Sistem informasi manajemen rumah sakit (SIMRS) merupakan sistem informasi terintegrasi yang disiapkan untuk menangani keseluruhan proses manajemen dan pelayanan rumah sakit. Penelitian ini bertujuan untuk menganalisis penerapan sistem informasi manajemen rumah sakit di RSUD Dr. Sam Ratulangi Tondano. Metode penelitian ialah studi kualitatif kasus melalui wawancara mendalam dan observasi dengan empat informan. Analisis data melalui tahap reduksi data, penyajian data dalam matriks, validitas hasil penelitian menggunakan triangulasi sumber dan metode hingga penarikan simpulan. Hasil penelitian mendapatkan pada indikator infrastruktur ialah kurangnya keter-sediaan komputer di setiap bagian dan kualitas jaringan internet yang belum memadai, disebabkan karena kurangnya anggaran alokasi untuk SIMRS. Pada indikator sumber daya manusia (SDM) didapatkan kurangnya tenaga IT yang sesuai kualifikasi dan kompetensi serta adanya ketidakdisiplinan waktu saat bertugas, dan tidak adanya sistem reward dan punishment yang tegas; hal ini justru mengganggu alur pelayanan di rumah sakit. Indikator sistem operasional prosedur sudah sesuai standar rumah sakit untuk menjalankan tugas tupoksi sesuai tugas masing-masing. Simpulan penelitian ini ialah penerapan SIMRS di RSUD Dr. Sam Ratulangi Tondano dari indikator infrastruktur dan SDM kualitasnya masih kurang, di sisi lain indikator standar operasional prosedur sudah baik yang diatur langsung oleh pimpinan rumah sakit. Kata kunci: sistem informasi manajemen rumah sakit; infrastruktur; sumber daya manusia; standar operasional prosedur